Development of a Nondestructive Quantitative Procedure for the Analysis of Gold in Jewellery - Yusoff M.S, Meor; Maarop, Hairunazifah; Noorul Ehsan, Muhd; Harun, Hishamuddin (Malaysian Journal of Science, 2002)
Malaysian standard on determining the purity of gold is based on the fire assay method. But this technique has several disadvantages such as it is destructive, long analysis time and can only determine a single element. Energy-dispersive X-ray Flourescence (EDXRF is an analytical technique offering a fast and simple elemental analysis. The technique is able to do analysis on a range of sample types from solids to liquids, powders, granules and films. Measurements can be done on the concentration range of parts per million (ppm) to 100%. One of the main benefits of EDXRF analysis is its ease of sample preparation. Precious metal analysis such as gold can be done by directly measured the sample on to the sample station. Every element present will be identified and also quantified for their concentrations.